1994
DOI: 10.1002/pat.1994.220050505
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of unsaturated polyester resins for large sized composites

Abstract: A series of unsaturated polyesters based on phthalic anhydride (PHA), maleic anhydride (MA), ethylene glycol (EG), diethylene glycol (DG), triethylene glycol (TG), propylene glycol (PG), styrene (Sty) and acrylonitrile (AN) were prepared. The molecular weights of the prepared polyesters were determined by end‐group analysis. The effect of the structure of the resin on its curing behavior has been investigated. On the basis of the experimental study, the following were concluded: (1) The maximum curing temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 12 publications
(4 reference statements)
0
19
0
Order By: Relevance
“…This in turn is reflected in T max and t max . It is well known that, as the number of curable double bond along the unsaturated polyester chain increases, the curing reaction becomes more exothermic and proceeds faster [27,28]. Mita and Kambe studied structural effects of unsaturated polyester resins on their curing behavior [29].…”
Section: Determination Of the Curing Exothermsmentioning
confidence: 99%
“…This in turn is reflected in T max and t max . It is well known that, as the number of curable double bond along the unsaturated polyester chain increases, the curing reaction becomes more exothermic and proceeds faster [27,28]. Mita and Kambe studied structural effects of unsaturated polyester resins on their curing behavior [29].…”
Section: Determination Of the Curing Exothermsmentioning
confidence: 99%
“…[28] The constituents of these polyesters and their designations are given in Table 1. Once the various glycols and acids were weighed and charged into a kettle, they were constantly agitated.…”
Section: Preparation Of Polyester Plasticizersmentioning
confidence: 99%
“…After the completion of polyesterification reaction, the prepared polyesters were subjected to vacuum evaporation (100 mmHg at 180 8C) in order to increase the molecular weights of polyesters and lower the acid value to below 25.0 (mg KOH/g resin) and also to get rid of any unreacted materials. [28] The products were then purified by dissolving in acetone and precipitation in petroleum ether (60-80 8C). The acid numbers (A) and hydroxyl numbers (B) (mg KOH/g resin) of the purified samples were determined [29] and applied in the calculation of the number average molecular weights M n of the synthesized polyesters by substitution in Equation (1).…”
Section: Preparation Of Polyester Plasticizersmentioning
confidence: 99%
“…So, the net result of this variation is an increase of the number of curable double bonds along the unsaturated polyester chains. It is well known [25][26][27][28][29][30] that the curing reaction gets faster and more exothermic with increasing double bond intensity per each unsaturated polyester chain. Horie et al [27] studied the effect of the chemical structure of unsaturated polyester resins on their curing behavior and reported that the final degree of curing under isothermal conditions increases remarkably with increasing amount of fumarate/maleate unsaturations per polyester chain.…”
Section: The Effect Of Ma Concentrationmentioning
confidence: 99%
“…This effect of the varying MA concentration on the curing behavior of unsaturated polyester resins is consistent with our data obtained previously on unsaturated polyesters synthesized from virgin materials. [29,30] The effect of PHBA concentration…”
Section: The Effect Of Ma Concentrationmentioning
confidence: 99%